Perceived social support as an offshoot of attachment style - Moreira J.; Silva M. F.; Moleiro, C.; Aguiar P.; Andrez M.; Bernardes, S.F.; Afonso, H. (Personality and Individual Differences, 2003)
Questionnaires were completed by college students (N=182), with the purpose of examining the role of adult attachment and social support as predictors of psychological distress. Factor analyses of the attachment and social support measures yielded three factors for attachment (Preoccupation, Avoidance, Dismissiveness), and two for social support (Intimate, Casual). Both types of support were significant zero-order predictors of distress, but intimate support effects were rendered non-significant when attachment style was controlled for. In contrast, attachment style (Preoccupation) exerted a significant additional effect after social support was controlled for. Analyses of interactions suggested that Preoccupation reduces the effect of Intimate Support, while Avoidance enhances the effect of Casual Support. These results support the hypothesis that perceived social support, and particularly Intimate Support is, to a large extent, a by-product of attachment style, but also point towards possible moderator effects of attachment style upon the impact of support.